Transformation of Salicylic Acid and Its Distribution in Tea Plants (Camellia sinensis) at the Tissue and Subcellular Levels - Li, Jianlong (Plants (Basel), 2021)
Salicylic acid (SA) is a well-known immune-related hormone that has been well studied in model plants. However, less attention has been paid to the presence of SA and its derivatives in economic plants, such as tea plants (Camellia sinensis). This study showed that tea plants were rich in SA and responded differently to different pathogens. Feeding experiments in tea tissues further confirmed the transformation of SA into salicylic acid 2-O-β-glucoside (SAG) and methyl salicylate. Nonaqueous fractionation techniques confirmed that SA and SAG were mostly distributed in the cytosol of tea leaves, consistent with distributions in other plant species. Furthermore, the stem epidermis contained more SA than the stem core both in C. sinensis cv. “Jinxuan” (small-leaf species) and “Yinghong No. 9” (large-leaf species). Compared with cv. “Yinghong No. 9”, cv. “Jinxuan” contained more SAG in the stem epidermis, which might explain its lower incidence rate of wilt disease. This information will improve understanding of SA occurrence in tea plants and provide a basis for investigating the relationship between SA and disease resistance in tea plants.